Islam on the street : religion in modern Arabic literature - Mūsawī, Muḥsin Jāsim (Rowman & Littlefield Publishers, 2009)
Islam on the Street deals with the popular side of Islam, from among the more militant groups in Islam, and by other, more secular thinkers who have also influenced public opinion. Muhsin al-Musawi explains the growing rift that has occurred between the secular intellectual and the upsurge of Islamic fervor in the street and what these secular intellectuals can do to reconnect with the masses.